PERBEDAAN LAMA PELEPASAN TALI PUSAT PADA BAYI YANG DIMANDIKAN KE DALAM AIR HANGAT DENGAN BAYI YANG DILAP HANDUK BASAH DI RSIA HUSADA BUNDA SALO - Dewi Sulastri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2018)
Newborn care that is often taught by health workers to mothers before returning from the hospital or maternity home is one of the ways of cord care. Paisal (2007, in Supriyanik, 2011) said that before the umbilical cord is released, the baby should not be bathed by dipping it in water. Simply wipe it with warm water. The reason is to keep the umbilical cord dry. If the umbilical cord is wet the chances of infection are greater because the wet umbilical cord is a good place to breed germs and bacteria including tetanus germ spores. The point is to let the umbilical cord be exposed to air so that the umbilical cord will dry quickly and loose. The benefits of good and correct umbilical cord care that is the umbilical cord will be released about 5-7 days after the baby is born without any complications (Saleha, 2009). Treatment intervention errors allow the baby to respond unwantedly, for example when performing cord care is not done regularly and not keeping the area around the umbilical cord clean will cause the umbilical cord to become wet and long dry. Another response that might be generated is the occurrence of umbilical cord infection which results in the umbilical cord being released longer. The purpose of cord care is to prevent infectious diseases such as tetanus neonatorum in newborns. Tetanus Neonatorum is tetanus disease in newborns with typical clinical signs, after the first 2 days the baby lives, cries and suckles normally, on the third day or more there is a full body stiffness characterized by difficulty opening the mouth and sucking, followed by seizures– seizure. The type of research used in this study is quasi experimental research. The design of this study uses Experimental Design-Equivalent Time Sample Population method and a sample of 60 people. Sampling using Accidental Sampling technique. The results of this study stated that there was a significant difference in the average length of umbilical cord release between infants with wet towel, which was 3.4 days with the baby bathed in warm water which was 5.03 days.